Penentuan Koefisien Transfer Massa Ekstraksi Pektin dari Buah Pepaya dalam Larutan HCl - Hesti Wijayanti (Universitas Lambung Mangkurat, 2007)
Indonesia has a great potency of papaya. As long as technology growth and demand in daily needs, its potency can be developed to get more value. One of the best ways is to extract pectin from papaya.This research conducted in order to obtain mass transfer coefficient in pectin extraction from papaya with HCl solution in stirred tank. Variables observed are extraction temperature, stirrer velocity and diameter of papaya powder.Extraction started by heating solution in batch reactor until wanted temperature achieved. Afterward turned on the stirrer motor with certain velocity. During the reaction, the temperature and the velocity of stirrer motor were kept constant. Sample was taken when certain time is reached.From this research, we got relation between mass transfer coefficient in pectin extraction from papaya with HCl solution in stirred tank and its influence variables, that could be written on this equation : = 1.033Or :Sh = 1.033 ( Re)0.716 (Sc )0.291 ( db/dp )-0.066with average relative error 3.2702 %.